MODEL EVALUASI PRODUK HUKUM DAERAH BERBASIS HUKUM TATA NEGARA DAN MAQASHID SYARIAH DALAM MEWUJUDKAN REGULASI YANG KONSTITUSIONAL DAN BERKEMASLAHATAN - Akhmad Zaki Yamani (INTELIGENSIA MEDIA, 2026)
This study is motivated by the growing complexity of regional legal products within the decentralization framework, which requires regulations to fulfill not only formal legality but also substantive public welfare objectives. The primary issue lies in the persistence of regional regulations that are inconsistent with higher-level legislation, potentially conflict with constitutional principles, and inadequately reflect societal benefits. This research aims to formulate an evaluation model for regional legal products based on Constitutional Law and Maqashid Sharia to promote regulations that are both constitutional and welfare-oriented. The study employs normative legal research using statutory, conceptual, philosophical, and comparative approaches. The findings reveal that existing evaluation mechanisms predominantly emphasize formal legal compliance and have not comprehensively assessed substantive public benefit. This research proposes a Constitutional-Maqashidi Evaluation Model integrating constitutionality, legality, and public welfare into a unified analytical framework. Theoretically, the model contributes to the development of regulatory evaluation studies. Practically, it offers policymakers and regional governments a systematic instrument for producing higher-quality, constitutionally compliant, and socially beneficial regulations.